PENGARUH FLUKTUASI HARGA EMAS, INFLASI, BI RATE DAN UKURAN PERUSAHAAN TERHADAP PEMBIAYAAN PRODUK GADAI EMAS BANK UMUM SYARIAH - Herman Paleni; Mulyadi Mulyadi; Suwarno Suwarno; Weli Paita Sari; Mia Erfiani (LPPM UNIVERSITAS BINA INSAN, 2020)
Islamic bank are bank that carry out business activites based on Islamic principles, namely agreements based on Islamic law between bank and customers in accordance with Islamic law. The function of the bank is as an intermediary between people who are over-funded and those who are short of founds. There are many product channeling founds in Islamic banking one of which is gold mortgage financing. In 2012, golg mortgage financing experienced a very high increase but in 203 as slight decline until finally the decrease in the financing of the lowest gold mortgage that is in 2015. This is what makes the author interested to comply with the reduction of gold mortgage financing. The method of analysis used in this research is the method of panel data regression analysis done with Eviews 8. One of the requirements to perform multiple analysis test needs to be tested classical assumption. It is necessary that the resulting regression equation be BLUE (Best, Linear, Unbiased, Estimator). In addition to assess the goodness of fit a model tested coefficient of determination, F test, and t test. This study uses quarterly data from 20012-2018 for each research variable. The results of this study indicate that the variable gold price fluctuations, the BI Rate has a negative effect on the financing of gold pawning products and the inflation variable has an effect on the financing of the gold price variables and firm size have a positive effect on the financing of gold pawning products.